The Role of English as a Global Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The significance of the English language has evolved considerably in the modern world. Originally spoken by a relatively small group of people, English has become a dominant global language that is widely used in business, education, technology, and international relations. This article explores the role of English as a global language, examining its historical development, current uses, and potential future. By analyzing the factors that have contributed to English's widespread adoption and discussing its impact on non-native speakers, the article highlights the linguistic, cultural, and economic consequences of English's status as a global lingua franca. It also considers the challenges and controversies that arise from the dominance of English, particularly in the context of linguistic diversity, cultural imperialism, and educational equity. Finally, the article offers a critical reflection on the future of English in a rapidly globalizing world.